Methodical guidance for master's diploma paper - Shestopalov, O. V.; Novozhylova, T. B.; Tykhomyrova, T. S.; Nechyporenko, D. I. (National Technical University "Kharkiv Polytechnic Institute", 2024)
The basis for methodological guidelines design for the diploma paper implementation in the field of "Ecology” at the Department of Chemical Engineering and Environmental Protection of the National Technical University "Kharkiv Polytechnic Institute" (NTU "KhPI") is STZVO-KhPI-2.01-2021 "Diploma projects and theses. General requirements for implementation" [1]. This standard establishes general requirements for the procedure for preparation, execution and defense of diploma projects and diploma theses (paper) for all levels of education.
Методичні вказівки до виконання дипломного проєкту другого (магістерського) рівня
Keywords: methodical guidance; master's diploma paper; ecology; foreign students; методичні вказівки; дипломні проєкти; магістерський рівень; екологія